A cross-sectional analysis of Zika virus infection in symptomatic and asymptomatic non-pregnant travellers: Experience of a European reference center during the outbreak in the Americas. Issue 27 (January 2019) - Huits, Ralph; Maniewski, Ula; Van Den Bossche, Dorien; Lotgering, Erica; Tsoumanis, Achilleas; Cnops, Lieselotte; Jacobs, Jan; Van Esbroeck, Marjan; Bottieau, Emmanuel
Abstract: Background: Zika virus (ZIKV) infection a concern to travellers because of potential sexual transmission and adverse pregnancy outcomes. Objective: To describe our experience in diagnosing ZIKV in travellers returning from endemic territories. Method: Travellers were evaluated for ZIKV at our clinic in a 12-month period during the outbreak, using ZIKV-specific RT-PCR and anti-ZIKV Immunoglobulin M/G ELISA when symptomatic, and ELISA only for asymptomatic travellers, preferably from 20 days after the last exposure. All positive ELISA results were subject to confirmation by Virus Neutralization Testing. We estimated post-test probabilities of ZIKV in asymptomatic travellers. Results: Of 462 travellers, 227 reported symptoms and 235 did not. Asymptomatic travellers had similar baseline characteristics, but were younger (median age 31 vs. 33 years, p = 0.01) and had reproductive concerns more often (75.8% vs. 24.2%). ZIKV infection was confirmed in 49 cases: 46/227 (20.3%) were symptomatic and 3/235 (1.3%) asymptomatic. Rash (positive likelihood ratio (LRP) 5.6) and conjunctivitis (LRP 10.8) predicted ZIKV infection. The post-test probability of a negative ELISA-result at 20–25 days was below 0.1%. Conclusion: ZIKV infection was frequent in symptomatic, but not in asymptomatic travellers. We consider negative ELISA results at 20–25 days after exposure a safe strategy to rule out ZIKV infection. Testing for ZIKV-specific antibodies within this timeframe could be particularly valuable in the management of returning travellers who wish to conceive.